Geographical spatial distribution and productivity dynamic change of eucalyptus plantations in China - Zhang, YuXing; Wang, XueJun (Scientific reports, 2021)
The Eucalyptus spp. is fast-growing and is usually harvested at a young age, which enables efficient and sufficient timber supply. However, its negative impact on soil fertility incurs wide debates. Therefore it is necessary to study on the growing traits of eucalytpus to provide scientific guidance on its plantation management and associated policy-making. In this study, we collected the sample plot data from 9 National Forest Inventories (NFIs) during 1973–2018, China Forest-Land Database Map in 2003 and 2016, as well as climate and elevation data and analyzed how the spatial distribution of eucalyptus plantations in China changes with time. We quantitatively characterized and evaluated the productivity, carbon accumulation capacity, and abandonment rate of eucalyptus plantations. Statistical models on how eucalyptus productivity and abandonment rate change with time are established to evaluate the soil fertility and feasibility for growing eucalyptus plantations and predict the temporal productivity variation. The results show that regions with annual mean temperature of 19–21 °C, annual precipitation of 1400–1600 mm, and elevation of 0–300 m above sea level is most suitable for the growth of eucalyptus. The annual mean productivity of eucalyptus plantations ranges from 4.14–8.57 m 3 hm −2 a −1 . Higher productivity (9.32–10.88 m 3 hm −2 a −1 ) could be reached in newly cultivated lands. Based on data from the 9th inventory (2014–2018), the mean carbon fixation of eucalyptus is 5.29 t hm −2 a −1 , which is 2.95 and 2.18 times greater than Pinus massoniana Lamb. and Cunninghamia lanceolata Lamb. Its plantations area accounts for 6.85% of total plantations in China, but it contributes to more than 17.96% of total annual cut from plantations. In Guangdong and Guangxi provinces, areas of eucalyptus plantations are 30.32% and 34.91% of the total plantation area in each province respectively, but eucalyptus plantations contribute to 66.29% and 49.97% of harvested timber stock volume Eucalyptus pla consumes soil fertility significantly. The cumulative abandonment rate (based on area) is about 25%, 50%, and 75% after 5, 10, and 20 years of growing eucalyptus, respectively. The soil fertility decreases significantly after 50 years of growing eucalyptus continuously. In such case, it is difficult to restore the soil fertility. It is suggested that with improved management measures such as proper crop rotation rotating crops properly, it is possible for the abandoned plantations to be reused for growing eucalyptus. Currently the rates of replanting eucalyptus are still below 20% and 30% after 20 and 50 years of without growing eucalyptus, respectively. Although the proportion of eucalyptus area replanted to its abandoned area is now less than 20% in 20 years and less than 30% in 50 years, there is potential to keep increasing the replanting rate. We argue that developing eucalyptus plantations could contribute to global timber supply, help to protect natural forests, increase global carbon storage and fixation, and help to slow down global warming. In conclusion, we should not stop growing eucalyptus despite its high consumption of soil fertility.